Acute shortening and double-level lengthening versus bone transport for the management of large tibial bone defects after trauma and infection. Issue 3 (March 2023) - Huang, Qiang; Ma, Teng; Xu, YiBo; Lu, Yao; Li, Ming; Wang, Qian; Ren, Cheng; Xue, HanZhong; Li, Zhong; Zhang, Kun
Highlights: We develop a new modified technique of acute shortening and double-level lengthening for the management of large tibial bone defects after trauma and infection. Compared with bone transport, our modified technique of acute shortening and double-level lengthening could reduce time in frame and postoperative complications. Abstract: Objective: The aim of this study was to present our experience with a new modified Ilizarov technique of acute shortening and double-level lengthening (ASDL) for the management of large tibial bone defects after trauma and infection and compare it with bone transport (BT). Methods: A retrospective comparative study was performed on 47 patients with large tibial defects after trauma and infection from June 2014 to June 2018. Depending on different Ilizarov methods, these patients were divided into ASDL group ( n = 21) and BT group ( n = 26). The difference in bone lengthening time, time in frame, external fixation index, docking site healing time were recorded and compared between the two groups. Bone and functional results were evaluated according to the Association for the Study and Application of the Method of Ilizarov (ASAMI) criteria. Complications encountered in both groups were categorized according to the classification of Paley, including problems (treated nonoperatively), obstacles (treated operatively), and sequelae (unresolved at last). Results: All patients were followed for at least two years since the lengthening frame was removed. All cases achieved complete union at the docking site and consolidation of the regenerate callus. The mean bone loss was 8.9 cm (range 6.5–16.0 cm) in ASDL group vs. 10.3 cm (range 5.2–18.5 cm) in BT group. The mean bone lengthening time was 2.4 ± 0.7 months in ASDL group vs. 4.1 ± 1.4 months in BT group ( p <0.001); time in frame was 9.1 months (range 7.0–14.5 months) in ASDL group vs. 17.7 months (range 13.5–23.0 months) in BT group ( p <0.001); and external fixation index was 1.04 months/cm (range 0.83–1.38 months/cm) in ASDL group vs. 1.91 months/cm (range 1.28–2.70 months/cm) in BT group ( p <0.001). The incidence of obstacles occurred in ASDL group was significantly lower than that in BT group ( p <0.001). There was no significant difference in the bone ( p = 0.635) and functional results ( p = 0.293) between the two groups. Conclusion: Compared with bone transport, our modified technique of acute shortening and double-level lengthening could reduce bone lengthening time, time in frame, external fixation index and postoperative complications. It showed better clinical effects in patients with large tibial bone defects after trauma and infection.